Modelling of LPG Ship Distribution in Western of Indonesia using Discrete Simulation Method - Trika Pitana; Saut Gurning; Fauzan Fikri (International Journal of Marine Engineering Innovation and Research, 2017)
The result of data from the Energy Outlook Indonesia issued by the National Energy Board, mentioned the demand of LPG every year continues to rise, and there is a regions has high increased still at western part of Indonesia, precisely in the Sumatra and Java Island. Because of that, so effort to necessary anassesment for remake case study on the distribution pattern of vesseles with the thechincal data on the loading port and discharging port. The data has affecting distribution pattern of vessels, will be used to replicate previously existing transport system currently operated by using discrete simulation method, evaluated, and scenario building improvements to variations number and size of the capacity of vessels to get distribution pattern of effective and efficient. The result of this research obtained scenario capable to meet the demands of each destination terminal port with a case study during the next 5 years and also which has a vesseles operating expenses are the most economical.